المسيرة النضالية للشهيد مواليد بخليفة المدعو " طاهر موسطاش" قائد المنطقة الخامسة من الولاية الخامسة التاريخية 1953- 1961م. (مجلة الواحات للبحوث والدراسات, 2020)
The Need To Study This Subject Was To Look For Those "Historical Actors" And Their Struggle In The Ranks Of The Algerian Liberation Revolution, As Highlighting The Importance Of The Fifth Region Of The Historical Fifth State Had A Great Impact In The Search For The March Of The Revolutionary Struggle, This Struggle That Moved The Algerian People Were In A State Of Disrething And Giving A One-Time Boost To Their Homeland's Independence And Get Rid Of French Colonial Domination.         It Is This Popular Rallying Around His Glorious Revolution That Has Given Rise To This Continuity In The Struggle Of The Mujahedeen, Despite The Use Of All His Political And Military Designs By The French Enemy In Order To Absorb The Determination Of This People And To Distance Them In Various Ways From This Revolution, Which Was The Source Of Their Struggle And Jihad.         The Permanent Presence Of Militant Leaders Such As Si Ben Allal, Si Abd Al Hadi, Si Issa Al-Bouzidi, And In Particular The Village Of Tajmut Tlemcen And Its Environs Gave The Advantage Of Revolutionary Activity At The Grass-Roots Level, Giving The Best Of The Villagers To Join The Ranks Of The Liberation Revolution. One Of Them Was Si Moualid Bekhlifa, The Latter Who Chose To Fight Under The Leadership Of Si Bin Alal, And Soon He Will Assume High Ranks As A Result Of His Work And Revolutionary Activity, Which Proved His Loyalty To His Country And His People.  Key Words- Moualid Bekhlifa, Tajmut Village, Revolutionary Activity, 1st District, 5th District.